Police Power and Race Riots : Urban Unrest in Paris and New York - Schneider, Cathy Lisa, 1955- (Book collections on Project MUSE., 2014)
Cathy Lisa Schneider looks at the relationship between racialized police violence and urban upheaval in impoverished neighborhoods of New York and greater Paris, and considers some of the changes that have made American cities less riot-prone today.